Kant’s Philosophical Context: Mendelssohn, Lessing and the Enlightenment - Genazzano, Pablo; Sales Vilalta, Guillem (Con-Textos Kantianos. International Journal of Philosophy, 2025)
This introduction aims to present the contents and objectives of the dossier Kant’s Philosophical Context: Mendelssohn, Lessing and the Enlightenment. The introduction situates the dossier within recent historiographical efforts to move beyond classical narratives that cast “pre-Kantian figures” as merely transitional. It highlights how the collected articles explore Wolffian metaphysics in context, Mendelssohn’s proofs of God’s existence, and his articulation of Jewish philosophy, alongside Mendelssohn and Lessing’s influence on aesthetics and early Romantic criticism. By tracing continuities and tensions from Wolff to Schlegel through a focus on Mendelssohn and Lessing, the dossier reconstructs the plural and dialogical character of Enlightenment thought, vindicating the enduring relevance of these figures for understanding the diversity and fruitfulness of eighteenth-century German philosophy.